2020
DOI: 10.1109/access.2020.3036219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Communication Aspects of Potassium Intracellular Signaling in Cardiomyocytes

Abstract: Cardiovascular diseases continue to be a leading cause of morbidity and mortality worldwide. Cardiomyocytes, as the elementary heart components, play a crucial role in maintaining a healthy heart by coordinating contractions throughout the heart muscle that lead to a heartbeat. This study aims to characterize fine-grained ionic-level manipulation of cardiomyocytes for the controlled electrical activity that will offer new insights within the medical field. We explore the concept of Molecular Communications (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Lu et al demonstrate that Hamming codes can achieve a coding gain down to a BER of 10 −9 compared with an uncoded system and that optimal Hamming code parameters exist [131]. Specifically, Lu et al [65], [131] found that (32,26) Hamming codes have the highest efficiency in terms of energy usage, while in contrast (63, 57) Hamming codes have the highest coding gain. Following Lu et al, the energy loss or saving ∆E for a coded MC system can be defined as [131]:…”
Section: Category Coding Approachmentioning
confidence: 99%
“…Lu et al demonstrate that Hamming codes can achieve a coding gain down to a BER of 10 −9 compared with an uncoded system and that optimal Hamming code parameters exist [131]. Specifically, Lu et al [65], [131] found that (32,26) Hamming codes have the highest efficiency in terms of energy usage, while in contrast (63, 57) Hamming codes have the highest coding gain. Following Lu et al, the energy loss or saving ∆E for a coded MC system can be defined as [131]:…”
Section: Category Coding Approachmentioning
confidence: 99%